Special pension schemes for workers in arduous and hazardous jobs: Functions and conditions to ensure equal treatment - Sergio Mittlaender (International Social Security Review, 2023)
Most jurisdictions grant differentiated and more beneficial treatment – usually in the form of early retirement, and commonly under special pension schemes – to workers in arduous or hazardous jobs. Several justifications for such treatment have been advanced, including i) compensating the worker for the hardship, ii) protecting the worker from the hazard, and iii) realizing the principle of equality in the distribution of costs and benefits in the social security system. This article analyses these functions from a socioeconomic perspective and explains how early retirement for workers in arduous and hazardous jobs is necessary to ensure equality by treating “unequals unequally”, and in proportion to their inequality. Moreover, this article presents a precise formula to calculate when a worker should be allowed to retire, so that workers in occupational domains with a shorter life expectancy do not systematically enjoy lower expected benefits from the pension system while having contributed the same amount. Implications for the design and desirability of special pension benefits are discussed.
Keywords: 300; pension scheme; eligibility; equal treatment; occupational safety; international; régime de pension; conditions d'ouverture des droits; égalité de traitement; sécurité au travail; international; regimén de pensión; elegibilidad; igualdad de trato; seguridad en el trabajo; internacional; Rentensystem; Anspruchsvoraussetzungen; Gleichbehandlung; Arbeitsschutz; international